Perspectives of Vulnerable US Hispanics With Rheumatoid Arthritis on Depression: Awareness, Barriers to Disclosure, and Treatment Options. Issue 4 (April 2015) - Withers, Mellissa; Moran, Rosalinda; Nicassio, Perry; Weisman, Michael H.; Karpouzas, George A.
Abstract : Objective: Despite the high prevalence of depression among vulnerable Hispanics with rheumatoid arthritis (RA), many do not disclose it or seek treatment. This study explored patient perceptions of depression, its association with their primary disease, barriers to disclosure, reasons for low utilization of mental health care resources, and culturally acceptable intervention approaches. Methods: Semistructured interviews were conducted with 46 participants with RA. Depression was evaluated using Patient Health Questionnaire 9 (PHQ‐9). Results: Thirty‐three percent of participants were moderately depressed at the time of the interview, based on PHQ‐9 score ≥10; 12 of 46 patients (26%) stated they were depressed regardless of PHQ‐9 score. Depression was perceived as a long‐term, severe problem leading to suicide. It was associated with weakness and character flaws, contributing to stigma and reduced likelihood of disclosure. Antidepressants were not acceptable; self‐reliance and interventions incorporating interpersonal connections were preferred. Systems‐related barriers to disclosure included lack of verbal screening, language barriers, limited clinic visit time, and lack of continuity of care, restricting trust with providers. Conclusion: Rectifying misconceptions, as well as providing education regarding the association between RA and depression, the continuum of symptoms, and the range of experiences incurred are needed to facilitate earlier recognition and reduce stigma. Use, duration, and goals of antidepressant therapy should be clarified. Providers should strive to establish trust and conduct in‐person depression screening to facilitate disclosure. Interventions with an interpersonal component, such as support groups or patient navigators, were preferred. Themes emphasizing coping strategies, stress reduction, positive thinking, self‐efficacy, and resiliency are likely to be most acceptable.